2006
DOI: 10.1074/jbc.m509184200
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Binding Activity of MutL Is Required for Methyl-directed Mismatch Repair in Escherichia coli

Abstract: The DNA binding properties of the mismatch repair protein MutL and their importance in the repair process have been controversial for nearly two decades. We have addressed this issue using a point mutant of MutL (MutL-R266E). The biochemical and genetic data suggest that DNA binding by MutL is required for dam methylation-directed mismatch repair. We demonstrate that purified MutL-R266E retains wild-type biochemical properties that do not depend on DNA binding, such as basal ATP hydrolysis in the absence of DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 45 publications
4
59
0
Order By: Relevance
“…A crystal structure of a C-terminal dimerization domain of E. coli MutL reveals a V-shaped dimer that plays critical roles in the activation of UvrD by MutL and in DNA binding by MutL (Guarne et al, 2004). The DNA binding activity of MutL has been shown to be essential for methyl-directed MMR in E. coli (Robertson et al, 2006a). The N-terminal ATPase domain and the C-terminal dimerization domain are connected to each other via a flexible peptide linker with the elbow of the dimerization domain at one end and the lid of the ATPase domain at the other.…”
Section: Mutation Avoidance and Post-replication Repairmentioning
confidence: 99%
“…A crystal structure of a C-terminal dimerization domain of E. coli MutL reveals a V-shaped dimer that plays critical roles in the activation of UvrD by MutL and in DNA binding by MutL (Guarne et al, 2004). The DNA binding activity of MutL has been shown to be essential for methyl-directed MMR in E. coli (Robertson et al, 2006a). The N-terminal ATPase domain and the C-terminal dimerization domain are connected to each other via a flexible peptide linker with the elbow of the dimerization domain at one end and the lid of the ATPase domain at the other.…”
Section: Mutation Avoidance and Post-replication Repairmentioning
confidence: 99%
“…E. coli MutL can bind to a 93 bp partial duplex DNA with an apparent KD of 25 and 2.8 nM in the absence and presence of ADPnP, respectively (10). The investigation of the DNA binding affinity of TmL by a double-filter method performed using 30-mer ssDNA and dsDNA showed the μM range of Kd for TmL binding to a 30 bp dsDNA in the absence or presence of ADPnP.…”
Section: Tml and Its Mutants Had Ssdna Binding Propertiesmentioning
confidence: 99%
“…Previous studies have indicated that MutL binds to ssDNA with nucleotide correlation (9,10). E. coli MutL can bind to a 93 bp partial duplex DNA with an apparent KD of 25 and 2.8 nM in the absence and presence of ADPnP, respectively (10).…”
Section: Tml and Its Mutants Had Ssdna Binding Propertiesmentioning
confidence: 99%
See 2 more Smart Citations